2022
DOI: 10.3389/fnins.2022.896880
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Alcohol and Stress Exposure Rewires Key Cortical Neurocircuitry

Abstract: Human adolescence is a period of development characterized by wide ranging emotions and behavioral risk taking, including binge drinking (Konrad et al., 2013). These behavioral manifestations of adolescence are complemented by growth in the neuroarchitecture of the brain, including synaptic pruning (Spear, 2013) and increases in overall white matter volume (Perrin et al., 2008). During this period of profound physiological maturation, the adolescent brain has a unique vulnerability to negative perturbations. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 170 publications
(257 reference statements)
0
9
0
Order By: Relevance
“…Adolescence is broadly defined as the transitional period between childhood and adulthood, marked by a variety of maturational changes throughout the body (Spear 2000). In the brain, the prefrontal cortex (PFC) is one of the last regions to finalize development, with a variety of morphological, functional, and neuromodulatory changes occurring throughout this period (Sicher et al, 2022). This critical and time-locked development may make the PFC a particularly vulnerable brain region to insults including alcohol use, as any events which interfere with typical PFC development may produce permanent and lifelong consequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence is broadly defined as the transitional period between childhood and adulthood, marked by a variety of maturational changes throughout the body (Spear 2000). In the brain, the prefrontal cortex (PFC) is one of the last regions to finalize development, with a variety of morphological, functional, and neuromodulatory changes occurring throughout this period (Sicher et al, 2022). This critical and time-locked development may make the PFC a particularly vulnerable brain region to insults including alcohol use, as any events which interfere with typical PFC development may produce permanent and lifelong consequences.…”
Section: Introductionmentioning
confidence: 99%
“…While acute risks include car accidents or alcohol poisoning, long-term consequences can include impaired development of the PFC. Studies in both rodent models and human adolescents have shown that alcohol consumption interferes with typical maturation of the prelimbic (PL) region of the PFC, potentially inducing permanent changes in PFC structure and corresponding behavioral aberrations (for review see Sicher et al, 2022). The effects of alcohol on the PL cortex seem to be age dependent, as alcohol consumption during early adolescence, but not early adulthood, increased the excitability of deep-layer cortical pyramidal neurons (Galaj et al, 2020).…”
Section: Introduction 11 Adolescence and Alcohol Misusementioning
confidence: 99%
“…Of particular concern are the potential long-term consequences of adolescent binge drinking on brain development. For example, increasing evidence from preclinical models demonstrates that a history of binge-like alcohol exposure during adolescence can lead to persistent changes in cognitive function in adulthood (Spear, 2018 ; Crews et al, 2019 ; Lees et al, 2020 ; Salmanzadeh et al, 2020 ; Sicher et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol is the most widely abused substance during adolescence, whether due to impulse, sensation seeking, social facilitation, or attempts to cope with the stress of this particular period of life (Bava and Tapert, 2010). Alcohol consumption rates remained high leading up to the COVID-19 pandemic, with over 4.2 million adolescents between the ages of 14 and 20 reporting binge consumption at least once in the month prior (Sicher et al, 2022). Alcohol exposure in adolescence can impart age-dependent, brain-related changes that present in adulthood as reduced resilience to stress-related neuropsychiatric dysfunction (Grant and Harford, 1995, Rohde et al, 2001, Bava and Tapert, 2010; Spear, 2018, Kyzar et al, 2016; Rohde et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, impoverished upbringing, poor familial/social support, and toxic environmental exposures can promote developmental trajectories that instead bias individuals towards inflexible and potentially maladaptive behaviors in response to stress and adversity later in life (Silbereis et al, 2016). Accordingly, adolescence is thought to be a particularly vulnerable period when exposure to stress, alcohol, or drugs of abuse disrupts brain development in ways that substantially increase the risk of developing stress-related disorders in adulthood, including posttraumatic stress disorder (PTSD), major depressive disorder, and substance use disorder (Fuhrmann et al, 2015; Sicher et al, 2022).…”
Section: Introductionmentioning
confidence: 99%